Wide-sense nonblocking Banyan-type switching systems based on directional couplers. - Vaez, M.M.
Directional couplers are capable of switching signals with multiple wavelengths. They are the ideal technology for building light-path switches to configure wavelength division multiplexing (WDM) transmission facilities. This technology, however, has a major constraint: crosstalk. Design of a strictly nonblocking directional coupler-based photonic switching system under a specified crosstalk constraint has previously been studied. The results indicate that a lower level of crosstalk can be achieved at a cost of some extra amount of hardware. In this paper, we show that if a simple rule is followed in setting up the connections, both the amount of hardware for nonblocking networks and the connection setup time can be greatly reduced. The resulting networks thus belong to the class of wide-sense nonblocking networks
Keywords: WDM transmission facilities; Connection setup time; Crosstalk; Directional couplers; Light-path switches; Photonic switching system; Wavelength division multiplexing; Wide-sense nonblocking Banyan-type switching systems